Approved lists of bacterial names - Skerman, V. B. D.; McGowan, Vicki F.; Sneath, Peter Henry Andrews, 1923-; International Committee on Systematic Bacteriology. Judicial Commission. Ad Hoc Committee; American Society for Microbiology (Washington, D.C : American Society for Microbiology, 1989)
Summary: "Names included in the approved List of Bacterial Names are the only names which are nomenclaturally valid as at the 1st January, 1980." Alphabetical arrangement under genera, species, and subspecies. Each entry gives names, original source, strain designation, and when applicable, reference to the 8th edition of Bergey's Manual of determinative bacteriology, 1974
"Reprinted from International journal of systematic bacteriology, volume 30: 225-420, 1980, with corrections"
Keywords: Bacteriology -- Nomenclature; Bacteria -- Classification